CORRELATION BETWEEN FACIOLINGUAL INCLINATION OF MAXILLARY CENTRAL INCISORS AND MOLARS WITH MAXILLARY AND MANDIBULAR MORPHOLOGY - Chughtai, Abdul Muqeet; Waqar Jeelani; Maheen Ahmed; Muhammad Aman (Journal of Ayub Medical College Abbottabad, 2024)
Background: The torque of maxillary incisors and molars forms an important component of smile esthetics. The inclination of these teeth may be affected by maxillary and mandibular dimensions. The study aimed to evaluate the correlation between the faciolingual inclinations of maxillary incisors and first molars with palatal width (PW), palatal depth (PD), maxillomandibular angle (MMA) and mandibular width (MW) using cone beam computed tomography scans. Methods: A retrospective analysis of cone-beam computed tomography (CBCT) images of 66 adult subjects (males-37; females-29) was performed. The Planmeca Romexis viewer 6.2.1 software was utilized to determine the faciolingual inclination of the maxillary central incisor (UIPP) and first molars (right-MMR; left-MML). The correlation of UIPP, MMR and MML with age, PW, PD, MW and MMA was determined using Pearson’s correlation. Results: The mean age of the sample was 32.8±11.4 years. The UIPP showed a mild negative correlation with age (r=-0.430; p<0.001). Only the PW showed a mild significant correlation with MMR (r=-0.287; p=0.019) and MML (r=-0.343; p=0.005). All the other maxillomandibular parameters had insignificant (p>0.05) correlations with the inclinations of maxillary incisors and molars. Conclusion: The current study concludes that the PW had a significant inverse correlation with bilateral maxillary molar inclinations. Other parameters such as MMA, MW and PD had no statistically significant correlation with incisors and molars inclinations.